Brain Cytokines and Chemokines: Roles in Ischemic Injury and Pain - Masabumi Minami; Takahiro Katayama; Masamichi Satoh (Elsevier, 2006)
Abstract.: Cytokines and chemokines were originally identified as essential mediators for inflammatory and immune responses. Enhanced production and release of cytokines/chemokines are observed also in the central nervous system (CNS) under diverse pathological conditions. There is growing evidence showing that brain cytokines/chemokines play crucial roles in the neuro-glio-vascular interaction underlying the pathology of various brain disorders and therefore are potential targets for development of novel and effective therapeutics for CNS diseases. Here the evidence of the involvement of cytokines/chemokines in ischemic brain injury and pain is reviewed. Keywords:: interleukin, astrocyte, microglia, excitotoxicity, neuro-glio-vascular interaction